Democracy and development in Asia - Croissant, Aurel; Lott, Lars (Research handbook on democracy and development, 2021)
This chapter examines the development-democracy nexus in Asia-Pacific. The notion that democracy is a function of socio-economic modernization has been one of the most dominant theoretical frameworks in democratization studies. Using a data panel for 20 Asian countries, instrumenting for economic development and using two-stage least squares regressions to account for endogeneity between democracy and income, we find only a weak effect of economic development on the level of electoral democracy in the region. Furthermore, electoral democracy is not statistically associated with the level of economic development in Asia. Contrary to this, state capacity is a main driver of economic development, when controlling for country and year effects and the level of democracy as well as the interaction between democracy and state capacity. Finally, we find a positive link between rule of law and economic development in Asia, which is consistent with the existing empirical evidence derived from global samples.
Gesehen am 01.04.2021